PENGARUH KUALITAS PELAYANAN DAN LOKASI TERHADAP KEPUASAN PELANGGAN PADA ROLAG CAFE DIPONEGORO SURABAYA - Gunawan, Nano; Kartika, Chandra (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2018)
This research is meant to examine the influence of service quality, price, and place to the customer satisfaction at Cafe Rolag Diponegoro Surabaya. The population of this research is all customers who have ever visited at Cafe Rolag Diponegoro Surabaya. The research samples has been obtained by using accidental sampling method. In according to the predetermined criteria 100 respondents who have ever visited Cafe Rolag Diponegoro Surabaya have been selected as samples. The analysis method has been carried out by using multiple linear analysis with SPSS application .The result of the model feasibility test which has been done by using F test has concluded that the research model is feasible to be used for the following analysis. Meanwhile the result of hypothesis t test (partial) shows that service quality has significant influence to the customer satisfaction.And place has significant influence to the customer satisfaction. Keywords: Service quality, place, and customer satisfaction.